DISTRIBUSI INTESITAS TURBULEN PADA BELOKAN SALURAN DENGAN DASAR TERGERUS - Sumiadi Sumiadi (Universitas Gorontalo, 2021)
The flow characteristics on the channel bend are very complex. The Centrifugal force causes an increase in secondary flow. Increased secondary flow triggers changes in the channel bed topography. This phenomenon is very possible to change the flow structure including turbulent intensity. This research aims to determine the distribution of turbulent intensity at eroded-bed channel bend and to compare whether the equations of the turbulent intensity distribution by Nezu (1977) are still valid. This research was conducted at the Hydraulic Laboratory using 180° curved open channels. The bed material is sand with a median diameter, 1 mm and a density of 2.67 gr/cm3. The flow in the approach section is uniform flow and changes to non-uniform flow in channel bend. Measurements were carried out on equilibrium conditions of bed material. 3D instantaneous velocity measurements are carried out at 8 cross sections using Acoustic Doppler Velocimeter (ADV). The results showed that due to the presence of secondary flow in the channel bend caused a change in turbulent intensity distribution. In general, the horizontal turbulent intensity is greater than the vertical turbulent intensity. While the turbulent intensity in the outer bank tends to be greater than the inner bank. Furthermore, the vertical distribution of turbulent intensity in the eroded channel bend does not follow the exponential equation proposed by Nezu (1977).Karakteristik aliran di saluran menikung sangat kompleks. Gaya sentrifugal menyebabkan peningkatan aliran sekunder. Peningkatan aliran sekunder memicu perubahan topografi dasar saluran. Fenomena ini sangat berpotensi mengubah struktur aliran termasuk intensitas turbulen. Penelitian ini bertujuan untuk mengetahui distribusi intensitas turbulen pada belokan saluran dengan dasar tergerus dan membandingkan apakah persamaan distribusi intensitas turbulen oleh Nezu (1977) masih berlaku. Penelitian ini dilakukan di Laboratorium Hidrolika menggunakan flume dengan sudut belokan 1800. Material dasar yang digunakan adalah pasir dengan diameter median 1 mm dan rapat massa 2.67 gr/cm3.Kondisi aliran pada saluran pengarah di upstream adalah seragam dan berubah menjadi aliran tidak seragam pada bagian belokan. Pengukuran dilakukan pada kondisi material dasar equilibrium. Pengukuran kecepatan sesaat 3D dilakukan pada 8 cross section menggunakan Acoustic Doppler Velocimeter (ADV). Hasil penelitian menunjukkan akibat adanya aliran sekunder pada belokan saluran menyebabkan terjadinya perubahan distribusi intensitas turbulen. Secara umum, intensitas turbulen horizontal lebih besar dibandingkan dengan intensitas turbulen vertikal. Sedangkan intensitas turbulen di sisi luar belokan cenderung lebih besar dari sisi dalam belokan. Selanjutnya, distribusi vertikal intensitas turbulen pada belokan saluran dengan dasar tergerus tidak mengikuti persamaan eksponensial yang diusulkan oleh Nezu (1977).